Impact of Social Media Marketing Elements on Brand Loyalty Mediated by Brand Trust and Brand Awareness on Two Instant Noodle Products in the Solo Raya TikTok Application - Dhea Amelia Oktariana; Moechammad Nasir (Majapahit Journal of Islamic Finance and Management, 2026)
This research examines how social media marketing influences brand loyalty among TikTok users in the Solo Raya region, with brand trust and brand awareness as mediating variables in the context of Indomie and Mie Sedaap products. Using an explanatory quantitative approach, primary data were collected from 200 respondents through structured online questionnaires and analyzed using the Partial Least Squares (PLS) method with SmartPLS 4.0. The results indicate that social media marketing has a significant positive effect on brand trust and brand awareness, which in turn strengthens brand loyalty. However, brand awareness consistently mediates this relationship, while brand trust only functions as a mediator under certain conditions. This study contributes by highlighting the differing mediating roles of brand trust and brand awareness in TikTok-based marketing and provides practical insights for FMCG brands in strengthening consumer loyalty through short-video platforms. Limitations include reliance on online survey data and a limited scope of variables.